The Mouse in Biomedical Research, Volume 1 : History, Wild Mice, and Genetics. - Fox, James G. (Elsevier, 2006)
History, Wild Mice, and Genetics provides information about the history, biology and genomics of the laboratory mouse (Mus musculus), as well as basic information on maintenance and use of mouse stocks. Mouse origins and relationships are covered in chapters on history, evolutionary taxonomy and wild mice.